Formador e professor de LI em um curso de formação continuada: resistências e deslocamentos na rel(ação) - Amanda da Conceição Barros Pereira (2020)
This study aims at investigating the relationship established between a teacher’s educator and English teachers in a Continuing Education (CE) course for English Language (EL) teachers who work for public schools in the metropolitan region of Belo Horizonte – Minas Gerais. In a more specific way, we aim to understand how the teacher’s educator and the English teachers constitute, between resistances and subjective movements, their discursive and subjective positions when relating in this continuing education context. The events investigated are also based on the experience of the researcher, as an English teacher of public schools, who participated in the referred course. Considering the interdisciplinary nature of the area of the Applied Linguistics (AL), we are supported by the principles of Discourse Analysis based on the studies of Michel Pêcheux. Our copus is formed by narratives and semi-structured interviews with the teacher’s educator and the English teachers. The analysis and the interpretation device of the corpus is based on the concept of enunciative heterogeneity (ALTHIER-REVUZ, 1998; 2004) and discursive resonances (SERRANIINFANTE, 2001). We analyzed the relationship established between the teacher’s educator and the English teachers during the Continuing Education course, how it was designed and what were the implications of this relationship. We also investigated, through the discourse of our participants, their representations of themselves and of the others, and the impact of these representations on their relationship. Results show that the conflict arising from the relationship between our participants was able to mobilize these subjects, leading them to different discursive positions and processes of subjective movements.